Analisis Passing, Control, dan Shooting Futsal Putri pada Pertandingan Liga Mahasiswa: (Analysis of Passing, Control, and Shooting Women's Futsal at the Liga Mahasiswa match) - Izha Lely Siswanti; I Dewa Made Aryananda Wijaya Kusuma Dewa (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2020)
Futsal game is a game that has one goal, namely, to be a winner by scoring goals and trying to prevent opponents from scoring goals in accordance with the rules of the game. This sport is in great demand by various groups that do not know their age, both men and women. Futsal sport is not just a sport that people are interested in implementing healthy lifestyles, but now, futsal has become a goal for achievement. The purpose of this study is to find out what percentage of successful passing and error, what percentage of successful passing and error, what percentage of success and error control, and what percentage of shooting on target and off target carried out by all UNESA female futsal players in four matches in the East Java Conference Season 7 Student League Data Collection techniques were obtained through video documentation observation. As for what was investigated was how much the success rate of team passing, how much the success rate of a team to control, and how much accuracy a team did shooting, in the team in the 2019 Regional Student League match. Namely the data was taken through video observations of the match and inputting data observation results on blank. The conclusion of this research is the success rate of successful passing is very high reaching 703 times (76%), the success rate of successful control reaches 748 times (86%), and the accuracy rate of shooting on target technique reaches 51 times (54%).